Legal and Ethical Issues in the Report Heritable Human Genome Editing - Cohen, I. Glenn (The Hastings Center report, 2021)
This essay discusses the new report, Heritable Human Genome Editing, by the National Academy of Medicine, the National Academy of Sciences, and the Royal Society. After summarizing the report, we argue that the report takes four quite bold steps away from prior reports, namely (1) rejecting an omnibus approach to heritable human genome editing (HHGE) in favor of a case-by-case analysis of possible uses of HHGE, accepting that HHGE is acceptable in some cases; (2) recognizing that the interest in having children who are genetically related to both would-be rearing parents is one that the regulation of HHGE should honor; (3) patterning a regulatory model for HHGE on the United Kingdom's approach to regulating mitochondrial replacement techniques; and (4) conveying skepticism that international regulation is possible while showing a strong preference for a default into national regulatory regimes for HHGE.